Job satisfaction and organizational commitment of the staff of the national youth center program, 2019 - Grandez Pastor, Lelis Percy (2021)
The main objective of the research is to determine the relationship between job satisfaction and the organizational commitment of the staff of the National Youth Center Program, 2019; being the pure or basic type, where the level was correlational, the design was non-experimental, the approach was quantitative. A census survey was applied to 50 workers, the instrument was the questionnaire. The results show that 55% of the staff consider that the level of "Job satisfaction" is fair. The component with the highest incidence was the “Job Challenge” and the one in which it was necessary to improve was the “Rewards”. Regarding the level of "Organizational commitment", 64% consider it to be regular, the most prominent dimension being "Regulatory commitment" and the one focused on improvement was "Continuous commitment".It is concluded that there is a positive and high relationship (value of Rho = 0,711 and a value of p = 0,000) between job satisfaction and organizational commitment.